Anthropomorphic phantom organ dose assessment using optically stimulated luminescence dosimeters unified in multi-detector computed tomography - Omar, Ratna Suffhiyanni (2020)
This study focuses on a comprehensive performance assessment of different types of Multi-Detector Computed Tomography scanners, with particular focus given to quality control (QC) performance tests based on data and dose mapping using an anthropomorphic phantom. The performance test of microStar InLight® reader recorded intrinsic precision within ? 2% of the manufacturer’s recommendation. The calibration of the thermoluminescence dosimeter (TLD-100™) and nanoDot™ optically stimulated luminescence dosimeter (OSLD) comprised of optical annealing (illumination), signal depletion, signal fading, the linearity of dose-response, sensitivity and energy dependence. The optical annealing procedure using five light sources showed that the compact fluorescent lamp (CFL) recorded the highest response, with an average signal loss of ~93% in 60 minutes illumination time compared to ultra-violet light (UV), light-emitting diode (LED), tungsten-halogen lamp (THL), and bright room office environment light (BRL). The screened nanoDot™ OSLDs recorded a low signal depletion loss, with an average decrease of 1.0% depletion per reading. The recorded signal fading showed that screened nanoDot™ OSLDs displayed a small signal fading (becoming stabilised after 12 days), compared to unscreened nanoDot™ OSLDs and TLD-100™. The linearity dose-response of TLD-100™ and nanoDot™ OSLDs for 0 to 500 mGy exposed dose recorded a linear regression of coefficient values of 0.99981 and 0.99868. The results were very close to the value of one; both dosimeters showed an excellent linear dose response for different absorbed doses. The computed tomography dose index (CTDIw) fulfils the manufacturer’s guidelines (< ±20%), thus revealing that the nanoDot™ OSLDs could be used as alternative to Unfors detector and indicating their similar dose detection potential for CT scan applications. By comparing the QC performance tests for overall locations and model names, all the recorded data for scan localisation, X-ray generators, radiation dosimetry, image display, hard copy output, quantitative accuracy, image quality, as well as scattered radiation and radiation leakage, from the year 2015 to the year 2019, remained within the optimum achievable standard. Both lung and thyroid doses found in this study for CT chest-abdomen and head-neck protocol respectively, are particularly high since both thyroid and lung are situated along the main beam. This is in agreement with the fact that radiation doses from diagnostic radiology for similar examinations and modality differ, depending on several magnitudes such as tube voltage, exposure time, tube current, slice collimation and pitch factor. This study proves the importance of altering CT scan parameters accordingly, to initiate the optimisation process of current imaging practice.